Ethnomathematics on Dayak Tabun Traditional Tools for School Mathematics Learning - Hartono Hartono; Marhadi Saputro (SAINTIS Publishing, 2018)
The purpose of this study was to describe ethnomathematics on Dayak Tabun traditional tools in school mathematics learning. This study uses a qualitative approach, with descriptive research methods. Observation techniques are direct observation and communication techniques, namely interviews with Dayak Tabun community leaders, especially makers, users, and traditional stakeholders. the results of the research obtained are: 1) form, learning context in geometric concepts, namely flat and wake up space; 2) aspects of the motive, the learning context in the geometry concepts, like are two-dimensional, lines, and angles, besides that the algebraic concept is a number pattern in the form of a constant sequence; 3) the way of making, the learning context in the algebraic concept of numbers, namely fractions in dividing the material into two parts, calculating operations especially on natural numbers, sequential numbers through measurement of materials; 4) in terms of the use of tools, the context of calculating operating learning is the tool used in the dance, namely the tapping of movements and elevation angles in trigonometric material, namely the use of a Sangkuh Akai tool. Therefore, ethnomathematics on traditional Dayak Tabun ethnic instruments can be used as the context of school mathematics learning.